Default and repayment among baccalaureate degree earners - Lance Lochner; Alexander Monge-Naranjo (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2014)
More than low default rates, lenders are interested in the expected return on their loans. In this paper, we consider a number of other measures of repayment and nonpayment that are likely to be of direct interest to lenders. Using data from the Baccalaureate and Beyond Longitudinal Study, we document repayment and nonpayment outcomes 10 years after grad- uation for American students receiving BA/BS degrees in 1993. We estimate differences in these outcomes across individual/family background characteristics, college major, type of institution, the amount borrowed, and post-graduation income. A key contribution is our analysis of the following outcomes in addition to student loan default rates: the fraction of the original undergraduate loan amount repaid as of 2003, nonpayment rates (including deferment and forbearance as well as default), and the fraction of original undergraduate loan amounts on which borrowers defaulted or are currently not repaying.
Keywords: 330; Student Loans; Default; Forbearance and Deferment; Labor Market Outcomes; Return to Lenders; Studienfinanzierung; Akademiker; Kredittilgung; Kreditrisiko; USA